Experimental investigation on fluidized bed jet grinding - Siti Masrinda Tasirin; Derek Geldart (1998)
Fluidized bed jet grinding is a well accepted method for producing powders with an average particle size of less than 10 μm quickly and effectively. Its use has increased steadily for grinding chemicals, minerals, pigments, pharmaceuticals, abrasives, plastics and food. Nevertheless, even though the uses are increasing, the basic mechanism of comminution within such mill is not well understood and their design and prediction of performance is therefore largely very empirical. Using coarse cracking catalyst and 2 mm i.d. jet nozzles, the effects of gas mass flowrate, separation distances and geometry of the set up on the initial grinding rate have been investigated. It was found that grinding was a consequence both of interparticle collisions in the jet region, and when a target plate was used, of abrasion on the single plate. For a given power input, target plate jet grinding gave a higher production rate and finer size of product than with two opposing nozzles